1998
DOI: 10.1007/s004410051127
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone-induced chondrocyte terminal differentiation in rat femur organ culture

Abstract: Thyroid hormone plays a role in skeletal maturation. The present study was undertaken to investigate the effect of thyroid hormone on growth and maturation of the epiphyseal cartilage in the rat femur organ culture system. The femora increased in both weight and size over time in culture in the absence of serum. The growth rate was suppressed by thyroxine treatment. Thyroxine induced chondrocyte hypertrophy in the area adjacent to the articular surface in the femoral condyle. In this area, the expression of ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…Sodium butyrate treatment resulted in hepatocytelike cells expressing glycolytic phenotype [115]. Thyroid hormones, steroid derivatives of cholesterol metabolism, have also been implicated as potent differentiation factors [116,117]. In addition, our recent findings indicate that glucosamine has chondrogenic effects on embryonic stem cells [118].…”
Section: Small Molecules-inmentioning
confidence: 66%
“…Sodium butyrate treatment resulted in hepatocytelike cells expressing glycolytic phenotype [115]. Thyroid hormones, steroid derivatives of cholesterol metabolism, have also been implicated as potent differentiation factors [116,117]. In addition, our recent findings indicate that glucosamine has chondrogenic effects on embryonic stem cells [118].…”
Section: Small Molecules-inmentioning
confidence: 66%
“…D2 activity has been demonstrated in the embryonic growth plate where it is regulated by the skeletal morphogen Hedgehog (20). Nevertheless, D2 activity was not identified in primary chondrocytes, growth plate tissue extracts, or primary organ cultures from postnatal animals (19,(21)(22)(23), suggesting a discrete role during embryonic development. In osteoblasts data are conflicting (16,18,24), although specific D2 activity was identified in whole bone and differentiated MC3T3 osteoblastic cells in one study (17).…”
mentioning
confidence: 93%
“…In vivo, thyroid hormones regulate expression of parathyroid hormone related peptide (PTHrP) and PTHrP receptors, which control the pace of chondrocyte proliferation during endochondral ossification . In organ cultures, thyroxine (T 4 ) is a potent stimulator of chondrocyte differentiation (Wakita et al 1998, Miura et al 2002, whilst in vitro T 3 decreases the growth of chondrocyte colonies and inhibits cell proliferation (Bohme et al 1992, Ohlsson et al 1992, Okubo & Reddi 2003. Many investigators have also demonstrated a positive role for T 3 in regulating terminal differentiation of chondrocytes in vitro in several species using different culture systems (Ohlsson et al 1992, Quarto et al 1992, Ballock & Reddi 1994, Bohme et al 1995, Alini et al 1996, Leboy et al 1997, Ishikawa et al 1998, Okubo & Reddi 2003.…”
Section: Introductionmentioning
confidence: 99%